A Exploration of Learners' Perceptions Regarding Key Dimensions of Second Language Writing (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This research considers the role and significance of the English language in the modern world. As a global lingua franca, English serves as the main medium of communication in business, science, technology, education, and international relations.